Relationship between Maximum Oxygen Consumption and Lactate Metabolism with Situational Efficiency of Highly Selected Young Judoists - Radakovic, R.; Radovanovic, D.; Nurkic, M.; Bratic, M.; Katanic, B. (SportMont, 2023)
Judo is often referred to as an explosive sport, which requires great anaerobic strength and capacity, with a well-developed aerobic system. Attaining a high level of physical fitness, strength, and fatigue tolerance is essential for achieving success in competition. Fatigue leads to decreased muscle strength, prolonged reaction time, reduced agility, neuromuscular coordination, overall body speed, concentration, and agility. The intensity at which this phenomenon occurs is known as the lactate threshold. The primary objective of the planned research was to establish a link between maximal oxygen consumption (VO2max), lactate metabolism, and the situational efficiency of selected young judoists. The sample consisted of 30 cadet and junior judo athletes from the national teams of Serbia (average age of 16.43±0.76 years, body height of 176.94±5.15 cm, and body weight of 69.71±10.64 kg). The research employed precisely standardized protocols and modern equipment to determine anthropometric characteristics, and the values of maximal oxygen consumption, lactate thresholds, and the index of a specific judo fitness test among the selected young judo athletes. Based on the obtained results, there was a moderate negative correlation between VO2max and the index of the special judo fitness test, as well as a low correlation between the first lactate threshold (PLAP) and the second lactate threshold (DLAP) with the index of the special judo fitness test (ISJFT). Additionally, a moderate negative correlation was found between VO2max and anthropometric parameters, while PLAP and DLAP exhibited low correlations with anthropometric parameters. The research results quantitatively illustrate the physiological adaptation of the top young judo athletes to the physical demands encountered during years of specific training. The proposed battery of tests can be utilized to assess the functional status of competitors more accurately and determine the competition profile for elite judo athletes.